THE HUMAS INJOURNEY AIRPORTS I GUSTI NGURAH RAI BALI DALAM MEMBENTUK PERSEPSI MASYARAKAT DI ERA DIGITAL: HUMAS INJOURNEY AIRPORTS I GUSTI NGURAH RAI BALI DALAM MEMBENTUK PERSEPSI MASYARAKAT DI ERA DIGITAL - maharani, riza; Yulyana Dewi, Ni Luh (Jurnal Pengabdian Kepada Masyarakat Ilmu Komunikasi, 2026)
Abstract This study aims to examine how the online public relations activities conducted by Injourney Airports at I Gusti Ngurah Rai Bali Airport shape public perception in the digital era. With the rapid development of digital technology and the high usage of social media, Ngurah Rai Airport utilizes digital platforms as effective means of interaction and communication with the public. This research highlights the digital public relations strategies implemented to enhance the airport’s image while simultaneously managing two-way communication with passengers, stakeholders, and the general community. The research method employed is qualitative, involving content analysis of social media activities and the official website of the airport. The results indicate that the use of digital media can strengthen positive public perception of the services and reputation of Ngurah Rai Airport, as well as improve engagement and real-time information transparency. These findings underscore the importance of public relations adaptation in the transportation sector in the digital era to achieve effective communication and build public trust. Keywords: Public Relations, I Gusti Ngurah Rai Airport Bali, Public Perception, Digital Era, Social Media